answersLogoWhite

0


Best Answer

0 is the identity element with regard to addition.

User Avatar

Wiki User

โˆ™ 2009-09-02 13:46:40
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.72
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
335 Reviews

Add your answer:

Earn +20 pts
Q: What property is 0 plus b equals b?
Write your answer...
Submit
Related questions

Which property says that a plus b equals b plus a?

The commutative property.


What property shows a plus b equals b plus a?

commutative property


What math property is a plus b equals b plus a?

commutative property


What is the name of the property for a plus b equals b plus a?

it is the associative property


CAN 0 plus equals B plus equals B?

Yes because if 1+0=1 than 0 plus b equals b


What is the answer to A plus B plus C equals A times B equals C?

A=0 b=0 c=0


What property states a plus b equals b plus a?

Commutative


Is a plus b equals b plus a illustrates identity property?

No.


What property is 2 plus 1 equals 1 plus 2?

The commutative property of addition. a + b = b + a


Is a plus b equals b plus a additive indentity?

no, it's the commutative property of addition.


Ax plus bx plus c equals 0?

x = -c/(a+b), provided a+b is not 0


What property is 9 plus l-bracket 9 plus 0 r-bracket equals l-bracket 9 plus 9 r-bracket plus 0?

This is the associative law for addition: If a, b, c are any numbers then: a + (b + c) = (a + b) + c


How do you solve a squared plus a plus ab plus b equals 0?

That factors to (a + 1)(a + b) a = -1, -b b = -a


If a plus b plus c not equal to 0 then a divided by b plus c equals b divided by c plus a equals c divided by a plus b prove that a equals b equals c?

Because there is no way to define the divisors, the equations cannot be evaluated.


What property is 8 plus 20 plus 12 equals 8 plus 12 plus 20?

Addition is commutative. That is, a + b = b + a for all a, b


The zero product property states that for all real numbers a and b if a times b equals 0 then?

Either a=0 or b=0


What is the property of 4 equals x plus y then x plus y equals 4?

Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y


What is the properties that justifies 3x plus 1 equals 1 plus 3x?

It is called the commutative property, a + b = b + a


Is 5 equals 5 plus 0 the symmetric property if not what property is it?

No, 5 = 5 + 0 is an example of the Zero Identity Property of Addition. The Symmetric property is a + b = b + a, so you're basically just reversing two terms and saying they're equal to each other.


How can you prove if a and b are real numbers then a plus b-a equals b?

Real numbers are commutative under addition (and subtraction) so a + b - a = a - a + b The set of Real numbers includes an additive identity, 0, such that a - a = 0 so a - a + b = 0 + b The additive identity also has the property that 0 + b = b [= b + 0] so 0 + b = b


What will be the X in terms of a and b if Cos aX equals 1 plus bX and a and b are constants?

a = 0, b = 0.


If x equals a-b y equals b-c z equals c-a then the value of x plus y plus z x plus y plus z is?

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0


If A plus B equals 0 what can you say about the components?

they are additive inverses


How -A multiplied by -B equals plus AB was determined and when?

A*(B-B) = A*0 = 0 Expanding the left hand side, using the distributive property, A*B + A*(-B) = 0 That is, A*B and A*(-B) are additive inverses. Next, (A-A)*(-B) = 0*(-B) = 0 Expanding, A*(-B) + (-A)*(-B) = 0 Therefore A*(-B) and (-A)*(-B) are additive inverses But, from above, the additive inverse of -A*B is A*B Therefore (-A)*(-B) = A*B It is not known when this was proven.


What is a plus c-b if a equals 3 b equals 5 and c equals 2?

a + c - b = 3 + 2 - 5 = 5 - 5 = 0